KUMBANG PREDATOR COLEOPTERA DI EKOSISTEM PERSAWAHAN DI DESA GUNUNG BATU, KABUPATEN OKU TIMUR - Astrid Sri Wahyuni Sumah; Ali Alamsyah Kusumadinata2 (BIOMA : JURNAL BIOLOGI MAKASSAR, 2024)
Coleoptera predatory beetles are one of the predators that inhabit the vegetation and soil surface in rice fields. Agricultural landscape simplification measures lead to the loss of important habitats for a diversity of predatory beetle species. One of the important roles of this beetle is to control agricultural pest populations during the rice season and fallow period. Thus, the aim of this research is to determine the species composition of predatory Coleoptera beetles in rice and fallow land ecosystems. The sampling method uses an insect suction machine and trap holes with three repetitions. The research results showed that there were 20 species of predatory beetles that had been identified consisting of 5 families, namely the Carabidae family (10 species), Staphylinidae (5 species), Coccinellidae (3 species) and Anthicidae (2 species). A total of 9 species of Coleoptera predatory beetles can be found in two ecosystems. The number of species found shows that biodiversity in the agroecosystem is still relatively stable due to vegetation and land management intensity. Thus, the predatory Coleoptera beetles in rice paddy ecosystems are still quite complex and diverse. So, predatory beetles can be used as biological control. Keywords: Beetles, predators, Coleoptera, rice fields, fallow fields